Juridical Consequences and Legal Protection for Unregistered Waqf Land - Shendy Rianti Islamy; Audia Andini Ariputri; Belinda Soegijanto; Willy Democitta Tanaya (LEGAL BRIEF, 2023)
This study aims to investigate the legal implications of unregistered waqf land and the protection available to it. The research adopts a descriptive and normative legal research approach to analyze the legal framework surrounding waqf in Indonesia. The findings show that the government has enacted laws and regulations, such as Law no. 5 of 1960, Government Regulation No. 28 of 1977 concerning Waqf of Owned Land, and Law Number 41 of 2004 concerning Waqf, to ensure that waqf assets are legally protected and registered. According to positive law, the waqf pledge deed is considered an authentic deed that can be used as evidence in resolving future disputes regarding waqf land. The involvement of witnesses in the waqf pledge process is essential to guarantee the protection of waqf land. Despite the existing regulations, there are still unregistered waqf lands that need legal protection. The research reveals that legal protection for unregistered waqf land is available in Indonesia. However, the absence of registration and certification for waqf land creates uncertainty and makes it vulnerable to misuse by parties who are not responsible for the legal nature and purpose of waqf. Therefore, it is important to continue promoting the registration of waqf assets to ensure their legal protection and prevent any future disputes. The implications of this research contribute to the ongoing discussions on waqf land registration and provide a basis for further research in this field.